Theoretical justification, practice and prospects of applied biotechnology in agronomy - S A Kornatsky; V V Vvedensky (RUDN Journal of Agronomy and Animal Industries, 2012)
The paper considers the possibility of disease-free crop in the practice of agriculture. Focuses on the problem points in the development of technologies of mass clonal micropropagation. On the example of the Russian Peoples' Friendship University demonstrated the benefit of a biotechnological laboratory for the development of innovative science, modern educational process and implementation of intensive technology.